The IMK's Model of the German Economy - Katja Rietzler (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2012)
This IMK Study is a documentation of the IMK's macro-econometric model of the German economy. Currently the model includes 48 behavioural equations, which are usually specified as error-correction equations, and 61 definitions. The model is based on seasonally unadjusted quarterly national accounts data complemented by additional statistics and calculations of the IMK. Special features of the model include a more detailed representation of the German exports by destination (euro area, UK, USA, rest of the world) as well as a Keynesian employment function. The model is used both for economic policy simulations and forecasts.
urn:nbn:de:101:1-201303149683
Keywords: 330